Effect of Hybrid Controller on a Heat Exchanger for Enhancing Heat Transfer Rate of Al2O3 Nanofluid - Vivekananthan, R. (Asian Review of Mechanical Engineering, 2021)
In this research paper, a hybrid controller is designed and developed which maintains the outlet temperature of a shell and tube heat exchanger by varying the cold water flow rate in such a way that conform the desired set value. Al2O3 nanofluid is mixed with water is to be used as the cooling fluid to increase the rate of heat transfer. PID controller only is not suitable for precise and a wide range of temperature control requirement. So that hybrid controller is designed and implemented by combining methods of fuzzy logic and PID controller’s concepts using Labview. Experiments were done on parallel flow shell and tube heat exchanger in a closed cycle system. The performance of the heat exchanger system is improved by a hybrid controller and the heat transfer rate is enhanced by aluminum oxide nanofluid.